2018
DOI: 10.1136/annrheumdis-2018-213625
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and socioeconomic impact of the rheumatic diseases on indigenous people: an invisible syndemic public health problem

Abstract: Epidemiological studies in Latin America suggest indigenous people lack proper healthcare for musculoskeletal (MSK) and rheumatic diseases.ObjectivesThis study aimed to estimate the prevalence of MSK disorders and rheumatic diseases in eight Latin American indigenous communities, and to identify which factors influence such prevalence using network analysis and syndemic approach.MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 43 publications
0
29
0
4
Order By: Relevance
“…A recent study exploring the prevalence of musculoskeletal disorders in Latin American indigenous communities demonstrated for the first time the close relationship between rheumatic diseases, comorbidities and socioeconomic conditions [73]. Among the American indigenous communities, diabetes comorbidity ranged from 0.7% to 10%, heart disease ranged from 1% to 18%, obesity ranged from 7% to 18%, and depression ranged from 5% to 12%.…”
Section: Are There Ia Syndemics?mentioning
confidence: 99%
“…A recent study exploring the prevalence of musculoskeletal disorders in Latin American indigenous communities demonstrated for the first time the close relationship between rheumatic diseases, comorbidities and socioeconomic conditions [73]. Among the American indigenous communities, diabetes comorbidity ranged from 0.7% to 10%, heart disease ranged from 1% to 18%, obesity ranged from 7% to 18%, and depression ranged from 5% to 12%.…”
Section: Are There Ia Syndemics?mentioning
confidence: 99%
“…American Indian and Alaska Native populations with RA also present more extra-articular manifestations, erosive disease and more severe radiographic findings, which are associated with a high frequency of HLA-B27 gene and subtype HLA-DRB1*1402. Additionally, indigenous population share similarities in difficulties in access to healthcare coverage, which may influence clinical outcomes 35,51,52 . Conversely, several studies showed that the frequencies of genetic alleles that increase RA susceptibility are more prevalent in Caucasians than in Africans.…”
Section: Discussionmentioning
confidence: 99%
“…Esta prevalencia también resulta similar a la reportada en estudios provenientes de Inglaterra, Lituania y América, mientras que la incidencia se encuentra en el rango menor de la tasa global (7,(34)(35)(36) . También es similar a lo reportado por Peláez-Ballesta et al en 2018, en un estudio que describió una prevalencia de AR de 1,3% en cuatro poblaciones indígenas de Latinoamérica; sin embargo, en un subanálisis del mismo estudio, la prevalencia en la comunidad indígena Qom de Argentina fue del 2,4% (37) .…”
Section: Discussionunclassified